KAJIAN TINGKAT PERKEMBANGAN TANAH PADA LAHAN PERSAWAHAN DI DESA KALUKU TINGGU KABUPATEN DONGGALA SULAWESI TENGAH - Ulfiyah A. Rajamuddin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The  objective of the research was to identify  the level of soil development in paddy soil in Kaluku Tinggu Village Donggala Regency Central Sulawesi. The method used in this research was a survey method in which observation and soil sample were taken systematically using a grid system.  The distance between observation points was 250 m.  The observation on soil sample distribution is carried out by using soil auger.  Soil profile for observation of soil morphological characteristics was determined based on the result of the soil auger data.  The data of soil resulted from field and laboratory analysis were used to compare soil characteristics among horizon.  The average of each parameter was calculated using formula of balance average. The morphological soil characteristics observation on paddy field showed that the profile thickness was 0-80 cm, horizon thickness  >12 cm, soil color was  grayish to grayish red, texture was sandy loam and clay loam, soil structure was granular and rounded blocky, and soil consistency were sticky and plastic. Such soil characteristics indicated that the soil development was at a recent stage.  A long period under submerged condition has impeded the soil development.